2010
DOI: 10.1007/s10661-010-1739-2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of polychlorinated biphenyls and organochlorine pesticides in wild mussels from two different sites in central Croatian Adriatic coast

Abstract: Levels of 24 organochlorine compounds were investigated in wild mussels collected at two locations (Krka estuary and Kaštela Bay) on the Croatian Adriatic coast in 2003, 2005, 2006, 2007, and 2008. PCB and OCP ranges found at the two locations overlapped and followed similar profiles despite the differences between the two locations indicating that they share a common pollutants source. Among organochlorine pesticides, the dominant compound was DDT. Among indicator PCBs, the dominant compound was PCB-153, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…Comparing ∑(α-, β-, γ-HCH) levels in shellfish from around the world, it is notable that the present concentrations were in the lower end in relation to data from east Asian waters (Ramu et al 2007b) and also compared to blue mussels from Greenland (Glasius et al 2005) (Table 2). However, comparing ∑(α-, β-, γ-HCH) levels presented herein with the European sampling sites (Kozul et al 2011; Van Ael et al 2012) indicated similar or only slightly higher levels (Table 2). It is reasonable to conclude that the high proportion of β-HCH together with low ratio of α-HCH/γ-HCH indicates that HCHs profile in shellfish was due to contamination of technical HCH together with lindane.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Comparing ∑(α-, β-, γ-HCH) levels in shellfish from around the world, it is notable that the present concentrations were in the lower end in relation to data from east Asian waters (Ramu et al 2007b) and also compared to blue mussels from Greenland (Glasius et al 2005) (Table 2). However, comparing ∑(α-, β-, γ-HCH) levels presented herein with the European sampling sites (Kozul et al 2011; Van Ael et al 2012) indicated similar or only slightly higher levels (Table 2). It is reasonable to conclude that the high proportion of β-HCH together with low ratio of α-HCH/γ-HCH indicates that HCHs profile in shellfish was due to contamination of technical HCH together with lindane.…”
Section: Discussionsupporting
confidence: 56%
“…d n.d.–5.4 d n.d.–0.34 d n.d. d n.d.–31 d n.d.–78 d (Giandomenico et al 2013)Scheldt estuary, Netherlands and Belgium2010Blue musselw.w.2.0–3.70.09–1.210–393.5–160.83–1.80.09–0.7651–360120–7600.28–5.2(Van Ael et al 2012)Adriatic coast, Croatia2003–2008Blue musselw.w.0.56–2.00.15–0.620.02–0.170.28–2.1(Kozul et al 2011)Baltic Sea, Finland2007Clamw.w.0.13–0.471.0–3.00.23–1.00.24–0.490.07–0.150.56–1.61.7–4.3(Pikkarainen 2007)Usuk, Greenland2000Blue mussell.w.2.06.1115.1134.17.1155.1(Christensen et al 2002; Glasius et al 2005) a Sum of 4,4′-DDT, 4,4′-DDE, and 4,4′-DDD b Sum of α-HCH, β-HCH, and γ-HCH c Sum of CB-28, CB-52, CB-101, CB-118, CB-138, CB-153, and CB-180 d n. d. not detected…”
Section: Discussionmentioning
confidence: 99%
“…Our results were very high compared with other findings recorded in the deeper waters of the Black Sea [ 34 , 35 ]. Other studies carried out in different seas have reported lower tissue levels of OCPs and PCBs compared with our results [ 36 , 37 , 38 ]. Heptachlor exceeded the MAC according to European legislation [ 32 ] at all sampling sites.…”
Section: Discussionsupporting
confidence: 75%
“…In particular, different Mytilus species (Mytilus edulis, Mytilus californianus, Mytilus galloprovincialis, Mytilus trossulus) and oysters (Cressostrea virginica) have been used to evaluate the contamination status of the US coasts. On the other hand, specimens from the genus Mytilus are historically used as sentinel organisms worldwide to monitor the contamination of some persistent organic pollutants (Monirith et al, 2003;Carro et al, 2005;Ko zul et al, 2011), heavy metals and organotin compounds (Chase et al, 2001;Furdek et al, 2012;Edwards et al, 2014), radionuclides (Ro zmari c et al, 2013;Kiliç et al, 2014) and more recently also emerging pollutants, such as pharmaceuticals . Mytilus is used also to evaluate the effect of pollutants on biota, which represents the second part of the environmental risk assessment (Forbes and Forbes, 1994).…”
Section: Introductionmentioning
confidence: 99%